Astrocytic TRPV4 Channels and Their Role in Brain Ischemia - Tureckova, Jana; Hermanova, Zuzana; Marchetti, Valeria; Anderova, Miroslava (International journal of molecular sciences, 2023)
Transient receptor potential cation channels subfamily V member 4 (TRPV4) are non-selective cation channels expressed in different cell types of the central nervous system. These channels can be activated by diverse physical and chemical stimuli, including heat and mechanical stress. In astrocytes, they are involved in the modulation of neuronal excitability, control of blood flow, and brain edema formation. All these processes are significantly impaired in cerebral ischemia due to insufficient blood supply to the tissue, resulting in energy depletion, ionic disbalance, and excitotoxicity. The polymodal cation channel TRPV4, which mediates Ca2+ influx into the cell because of activation by various stimuli, is one of the potential therapeutic targets in the treatment of cerebral ischemia. However, its expression and function vary significantly between brain cell types, and therefore, the effect of its modulation in healthy tissue and pathology needs to be carefully studied and evaluated. In this review, we provide a summary of available information on TRPV4 channels and their expression in healthy and injured neural cells, with a particular focus on their role in ischemic brain injury.
Keywords: Astrocytes; Cerebral Infarction; Humans; Central Nervous System; lidé; cerebrální infarkt; astrocyty; centrální nervový systém; TRPV Cation Channels; Brain; kationtové kanály TRPV; mozek; Brain Ischemia; ischemie mozku